Research and publication trends in environmental, social and governance (ESG), sustainable and responsible investment (SRI) and Maqasid Shariah framework between 2012-2021/ Muhammad Ridhwan Ab. Aziz ... [et al.] - Ab. Aziz, Muhammad Ridhwan; Mat Noor, Fauzias; Marzuki, Ainulashikin; Ali Basah, Mohamad Yazis; Sabri, Hisham; Ramli, Nur Ainna; Shahwan, Syahidawati (Faculty of Information Management, 2022)
People's perceptions of the necessity of financial management have changed as a consequence of global crisis. The consequence of this circumstance not only jeopardises a country's stability, but if it cannot be avoided, it might have an impact on the community's crime rate. The necessity for investment has benefited society and the government in their efforts to achieve long-term financial stability, and it may also improve quality of life. The objective of this article is to analyze research and publication trends in environmental, social and governance (ESG), sustainable and responsible investment (SRI) and Maqasid Shariah framework between 2012 to 2021. The methodology that has been applied in this article is descriptive research based on document analysis on previous research and publication on environmental, social and governance (ESG), sustainable and responsible investment (SRI) and Maqasid Shariah framework either from free-of-charge or free-of-registration online journals. The journals and articles are acquired from various sources of channel such as google scholar, science direct and researchgate.com. 211 articles have been collected and examined for the purpose of this research. This study perceived at several variables which include authorship trend, number of articles published, research technique, geographical affiliation, issue, and author gender. The general finding of this study illustrates that most of the previous study discussed on ESG disclosure and social responsible investment, while only limited number of research and publication have been discussed and published on Maqasid Shariah framework related to ESG and SRI.